EFFORTS TO IMPROVE UNDERSTANDING OF THE CONCEPT OF THE PHYTAGORAS THEOREM USING THE JIGSAW TYPE COOPERATIVE LEARNING MODEL IN CLASS VIII - Annisa Gustiani; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2020)
Lack of understanding of students' mathematical concepts in restating a concept, classifying objects according to specific properties according to the concept, giving examples and not examples of a concept, presenting concepts in various forms of mathematical representation, developing the necessary and sufficient conditions of a concept, and applying the concept or logarithm of problem-solving is a problem that is often encountered in students. This study aims to improve the understanding of the concept of the Pythagorean theorem of class VIII D even semester in SMP Negeri 1 Pleret, Bantul Regency. This type of research is Classroom Action Research (CAR). The research setting was class VIII D in the even semester of SMP Negeri 1 Pleret, Bantul Regency in the academic year 2019/2020, with 31 students. Data collection methods: observation, tests, interviews, and field notes. Research instruments: observation sheets, Pythagorean concept understanding test questions, interview guidelines, and field notes. The test instrument used was the content validity test. Data analysis using descriptive qualitative. The results showed that learning mathematics using the Jigsaw cooperative learning model could improve students' understanding of concepts. The average percentage of understanding concepts can show this: (1) the average percentage of understanding of concepts based on observations in the first cycle was 87.50% with moderate criteria, then increased cycle II to 93.75% high category. (2) the average percentage of concept understanding based on concept understanding tests in the first cycle was 59.34%, and then it increased in cycle II to 74.13%. The results of interviews with students showed that students enjoyed learning using the Jigsaw cooperative learning model.